Pemberdayaan Orangtua dan Guru dalam Meningkatkan Atensi Anak Autis Spectrume Disorder di Sekolah Autis Mitra Ananda Padang: Empowering Parents and Teachers in Increasing the Attention of Children with Autistic Spectrum Disorders at the Mitra Ananda Autism School in Padang - Edyyul, Ilham Akerda; Sari, Yuli Afmi Ropita; Gustina, Sri Rahmi; Khalida, Rahmi; Izzati, Maghfira Nurul; Aprilia, Melva (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Developmental disorders of joint attention or attention are the main characteristics of children with autism spectrum disorder (ASD). Therefore, it is essential to develop these skills in early intervention efforts. Empowering parents and teachers is essential for success in increasing the attention of children with ASD; parents and teachers play an essential role in programs for treating children with ASD. This service explores techniques for empowering parents and teachers to increase attention to children with ASD. Establishing communication and cooperation between parents and teachers is carried out by the management of the Ananda Padang Autistic Partner School. The methods used in this community service activity include lecture, question and answer, discussion, and practice methods. The aim is to provide education to increase the understanding of parents and teachers in increasing the attention of children with ASD. The activity was carried out from 13 and 14 October 2023 with nine parents and nine teachers. There was an increase in scores on the post-test after clients were given education about increasing attention in children with ASD, namely from an average of 2.78 to 4.80. Parents and teachers also felt satisfied with the activities carried out, with an average score for material quality of 6.05, media of 5.60, and benefits of activities of 5.20. The output of this activity is an increase in the knowledge of parents and teachers after receiving education, namely an increase in the average post-test score. The activity info link can be seen at https://forumsumbar.com/berita/38383/tim-pkm-mercubaktijaya-berdayakanorangtua-and-teachers-in-improving-children's-attention-asd/